Detoxification of Yam Tuber (Dioscorea hispida Dennst.) by Limited Heating in Yam Flour Processing - Harijono, Harijono; Sari, Tassa Agustriana; Martati, Erryana (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Yams is one of the tuber crops in Indonesia. Meanwhile, people still unaware to consumed it and its derivative product because of the toxic compound such as alkaloid (dioscorin) and also cyanide. For that, it is necessary to have a detoxification process so we can have any alternative products from yams which is safe to consumed, for example in the production of yams flour. Detoxification in this research using limited heating method. The limited heating in this research adopted curing method which is commonly used in several food commodity, therefore it could give optimized condition for several endogenous enzymes which contain in yams, one of the function of the enzymes is for decomposing cyanide precursor in yams. Result showed that curing time in 50ºC had significant difference on moisture content, free cyanide content in flour, free cyanide content in yams tuber after curing, starch content, total sugar, crude fiber, and color. But for pH parameter of yams tuber after curing, the result did not show any significant difference. The best treatment based on physicochemical parameters was the yams flour using curing time of 12 hours in 50ºC. The characteristics of that yams flour are: moisture content 6,30%, free cyanide contents 13,67 ppm, starch contents 56,42%, crude fiber 3,03%, total sugar 4,91%, rendement yield 26,74%, L* colour 72,20, a* 9,90, b* 21,07, hygroscopicity 2,57%, and gelatinization temperature of 81ºCKeyword: detoxification, yams flour, curing, endogenous enzyme